The Effects of Mouth Bacterial Infection on Saliva Flow - Mohammed F. Jubaz; Rawaa M. Mohammed; Syoof Khoman Alwan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Mouth bacterial infections most probably due to dental cares are a prevalent disease. Salivaryflow rate is affected by many diseases but there is not enough published data about the effect of mouthbacterial infection on the salivary flow rate. Objective: this study examines the relationship between salivaryflow rate and mouth bacterial infection in adult population. Methodology: cross sectional study. Result:salivary flow rate is affected by mouth bacterial infection as it is founded to be very low flow rate in 17% andlow flow rate in 40% of the sample population. Conclusion Salivary flow rate is affected by oral bacterialinfections that need urgent medical intervention to improve the outcome of those patients.